2019
DOI: 10.1177/0890334419851801
|View full text |Cite
|
Sign up to set email alerts
|

Breastfeeding Duration and Infant Sleep Location in a Cohort of Volunteer Breastfeeding Counselors

Abstract: Background Debate about mother and infant bed sharing has been polarized between supporters of bed sharing and public health policies that attempt to mitigate the risk of Sudden Infant Death Syndrome. Differences in group demographics may be an important aspect in co-sleeping acceptability. Research aims The first aim of this study was to investigate infant sleeping location in a dataset of mothers with strong breastfeeding outcomes. The second aim was to investigate the association between infant sleeping loc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Further, they found that infant sleep location had a significant association with breastfeeding. Five studies reported that infants who co-slept were more likely to be exclusively breastfeed at 6 months [43,66,103,104,142]. As described in the previous section, many studies found a significant relationship between bed-sharing and breastfeeding [43,55,66,103,104,133,142].…”
Section: Breastfeedingmentioning
confidence: 90%
See 2 more Smart Citations
“…Further, they found that infant sleep location had a significant association with breastfeeding. Five studies reported that infants who co-slept were more likely to be exclusively breastfeed at 6 months [43,66,103,104,142]. As described in the previous section, many studies found a significant relationship between bed-sharing and breastfeeding [43,55,66,103,104,133,142].…”
Section: Breastfeedingmentioning
confidence: 90%
“…A recent Australian study found that 33% of participants reported bed-sharing at 0-1 month; however, by 6-12 months, the prevalence of surface sharing had increased to 58% [43]. Conversely, Krouse and colleagues [97] reported that in their longitudinal descriptive study of an American cohort, bed-sharing with an adult caregiver decreased from 47% at one-month-old to 17% at three-months-old, while no mothers had intended to bed-share.…”
Section: Infant Sleep Location: Room-sharing and Surface Sharingmentioning
confidence: 98%
See 1 more Smart Citation
“…The most consulted topics within LactApp are related to critical issues regarding when women stop BF. The critical issues that stand out are related to the "baby's sleep", a topic that different authors note as important in relation to the establishment and maintenance of BF 30 . Also noteworthy is the lack of training that health professionals have regarding safe sleeping and its importance, both in the prevention of sudden infant death syndrome and with the maintenance of BF [31][32][33] .…”
Section: Discussionmentioning
confidence: 99%
“…Recent research underscores a strong association between breastfeeding outcomes and proximity of the infant to the mother (Bailey et al, 2020 ). In this regard, swaddling might be considered a double‐edged sword: the visual obscuring or suppression of feeding cues means that crying is one of the few behaviors a swaddled infant can adopt to communicate their hunger.…”
Section: Introductionmentioning
confidence: 99%